Plagiarism, Cheating and Research Integrity: Case Studies from a Masters Program in Peru - Carnero, Andres M. (2016)
Plagiarism is a serious, yet widespread type of research misconduct, and is often neglected in developing countries. Despite its far-reaching implications, plagiarism is poorly acknowledged and discussed in the academic setting, and insufficient evidence exists in Latin America and developing countries to inform the development of preventive strategies. In this context, we present a longitudinal case study of seven instances of plagiarism and cheating arising in four consecutive classes (2011–2014) of an Epidemiology Masters’ program in Lima, Peru, and describe the implementation and outcomes of a multifaceted, “zero-tolerance” policy aimed at introducing research integrity. Two cases involved cheating in graded assignments, and five cases correspond to plagiarism in the thesis protocol. Cases revealed poor awareness and high tolerance to plagiarism, poor academic performance, and widespread writing deficiencies, compensated with patchwriting and copy-pasting. Depending on the events’ severity, penalties included course failure (6/7) and separation from the program (3/7). Students at fault did not engage in further plagiarism. Between 2011 and 2013, the Masters’ program sequentially introduced a preventive policy consisting of: (i) intensified research integrity and scientific writing education, (ii) a stepwise, cumulative writing process; (iii) honor codes; (iv) active search for plagiarism in all academic products; and (v) a “zero tolerance” policy in response to documented cases. No cases were detected in 2014. In conclusion, plagiarism seems to be widespread in resource-limited settings and a greater response with educational and zero-tolerance components is needed to prevent it.